Tribological performance of self‐lubricating polyurethane elastomer compounding with the modified ultra‐high molecular weight polyethylene. Issue 7 (28th May 2021) - Xu, Bo; Yin, Bifeng; Li, Qianzhu; Kuang, Xin; Jia, Hekun
Abstract: Ultra‐high molecular weight polyethylene (UHMWPE) powder was modified by surface treatment technology, then its wettability, dispersibility, mechanical, and tribological properties in polyurethane elastomer were studied. The testing results showed that after surface treatment, UHMWPE powder could infiltrate and disperse evenly in polyurethane, and build micro cross‐link with the contact surface of polymer substrate, which is conducive to enhancing the internal stress of polymer and improving the mechanical properties. With a small amount of modified UHMWPE being added into the casting polyurethane (CPU) elastomer, the right‐angled tearing strength increases and the abrasion loss decreases. Moreover, the elastomer surface self‐lubricating performance of CPU compounding with modified UHMWPE is enhanced: compared with the neat CPU sample, the average friction coefficient of the CPU samples with 5%, 10%, and 15% of modified UHMWPE is reduced by 46.3%, 41.5%, and 39.0%, respectively, and the surface wear resistance is improved; under the high‐load working condition, the CPU elastomer with 5% of modified UHMWPE has the optimal tribological performance. Abstract : Ultra‐high molecular weight polyethylene (UHMWPE) powder was modified and dispersed in polyurethane, building micro cross‐link with the contact surface and enhancing internal stress of the polymer. With a small amount of modified UHMWPE compounding with the casting polyurethane (CPU), the mechanical properties and tribological performance of CPU elastomer were enhanced with the lower friction coefficient and higher surface wear resistance.